Dynamic collective choice with endogenous status quo - Wioletta Dziuda; Antoine Loeper (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2012)
This paper analyzes an ongoing bargaining situation in which preferences evolve over time and the previous agreement becomes the next status quo, determining the payoffs until a new agreement is reached. We show that the endogeneity of the status quo exacerbates the players' conflict of interest and decreases the responsiveness of the bargaining outcome to the environment. In some cases, it can lead the negotiations to complete gridlock. Compared to a bargaining protocol with an exogenous status quo, the status quo stays in place more often and equilibrium welfare is lower. In a legislative setting, this model shows that the inertial effect of the endogenous status quo can be mitigated by concentrating decision power, and can be eliminated by sunset provisions.
Keywords: C73; D72; D78; 330; dynamic voting; endogenous status quo; partisanship; polarization; policy inertia; sunset provision; checks and balances